FACTORS INFLUENCING ENGLISH LEARNING MOTIVATION: A STUDY OF THE PERSPECTIVES OF NON-ENGLISH MAJORS AT A PUBLIC UNIVERSITY IN HANOI, VIETNAM - Ngoc My Trinh (Tạp chí Khoa học Đại học Đà Lạt, 2024)
The purpose of this study was to explore the internal and external factors that motivate university students to learn English. The subjects were 30 non-English majors at a university in Hanoi, Vietnam, who had completed at least three semesters of university-level English. All of the students participated in semi-structured interviews. The interviews revealed that extrinsic orientation, teachers, and peers substantially improved learning persistence among the students, while unattractive learning materials and a lack of authentic communicative activities contributed to learning demotivation. The study also provided insightful recommendations to enhance student motivation in the EFL classroom.